Kajian Permasalahan dan Potensi Perilaku Ibu Dalam Pemberian Makanan Bagi Anak Dalam Kaitannya Pada Kualitas Hidup Anak-anak Yang Tidak Berkecukupan Gizi Di Keluarga Miskin Perkotaan - Hati, Getar; Adi, Isbandi Rukminto (UI Scholars Hub, 2014)
This article discusses about child welfare issues in a community related to mothers’ behavior child welfare issues of a community related to children of age 6-24 months with insufficient nutrition condition. It also describes about the factors which influenced to this condition that would be base of intervention design to solve the problems. This is an descriptive research. This research stated that parents, especially mother has the most important roles in determining their children’s life quality.